Structure of D-DNA: 8-fold or 7-fold helix? - Ramaswamy, N (1983)
We have shown that both right- and left-handed uniform helical models (RU and LU models) could be built to give satisfactory agreement with the fibre diffraction data of poly[d(I-C)] in the D-form. Atomic coordinates of these two models are reported in the present work. Molecular transforms of these two models, as well as of the recently published Hoogsteen base-paired 7-fold helical structure of Drew and Dickerson, are given. In view of the work of Drew and Dickerson, attention is drawn to the presence of clear 004 and 008 reflections in the diffraction patterns of poly[d(I-C)] and poly[d(A-T)]. The available data strongly suggest an 8-fold helical structure for the D-form of DNA.